Rules and rituals in medieval power games - Althoff, Gerd (Brill, 2020)
Part 1. Introduction – What exactly are Spielregeln? – Spielregeln and rituals – Spielregeln, order of rank and conflicts – Part 2. Rules – Authority and violence of kings in tenth and eleventh century Germany – Rules of conflict among the warrior aristocracy of the High Middle Ages – Openness and secrecy : two fundamental categories of medieval communication – Saxon bishops in the tenth and eleventh centuries : strategies and rules of their political activities – The perspective of an expert : Gislebert of Mons – Part 3. Rituals – Rituals and their
Includes bibliographical references and index
Keywords: Political customs and rites; Nobility